2002
DOI: 10.1029/2001ja900177
|View full text |Cite
|
Sign up to set email alerts
|

Net field‐aligned currents controlled by the polar ionospheric conductivity

Abstract: [1] The results of an analysis of the east-west magnetic variations at midlatitudes suggest that the net field-aligned currents, which are the integral of the downward and upward field-aligned currents along a meridian, are strongly controlled by the polar ionospheric conductivity. The east-west magnetic disturbances at midlatitudes are expected to be the magnetic effects of the net fieldaligned currents in the polar region. We have examined the relation between the auroral electrojet intensity represented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The afternoon R1 and R2 current density maxima move from afternoon daytime in summer to the dark pre-midnight sector in winter, suggesting a redistribution of the FACs in response to the nightside location of particle produced, enhanced ionospheric conductivity. This redistribution of FAC to the nightside may also explain the increased FAC intensities near midnight during winter relative to summer observed by Nakano et al (2002) and Ohtani et al (2005a). The transfer of FAC from the dayside in summer to the nightside in winter also appears to have an IMF dependence.…”
Section: Summary Of Seasonal Fac Observationsmentioning
confidence: 73%
“…The afternoon R1 and R2 current density maxima move from afternoon daytime in summer to the dark pre-midnight sector in winter, suggesting a redistribution of the FACs in response to the nightside location of particle produced, enhanced ionospheric conductivity. This redistribution of FAC to the nightside may also explain the increased FAC intensities near midnight during winter relative to summer observed by Nakano et al (2002) and Ohtani et al (2005a). The transfer of FAC from the dayside in summer to the nightside in winter also appears to have an IMF dependence.…”
Section: Summary Of Seasonal Fac Observationsmentioning
confidence: 73%
“…Moreover, observations from ground were also in the favor of the feedback conductivity mechanism. Nakano et al (2002) analyzed local characteristics of the geomagnetic field to extract information on the field-aligned current variation. They showed that the net field-aligned currents are upward in the nightside region and downward in the dayside.…”
Section: Discussionmentioning
confidence: 99%
“…We used the standard deviation within 2100–0300 MLT in this procedure because we can ensure that the variations of Δ D within this MLT range contain little ionospheric current effects and that they are regarded as pure field‐aligned current effects. We must also consider a seasonal dependence of Δ D as indicated by Nakano et al [2002] because the seasonal dependence may cause the difference in Δ D between the two hemispheres to affect the MLT profile of Δ D derived from the data obtained in both of the hemispheres. In order to avoid this problem, we analyzed events around the equinoxes in this paper except for a statistical analysis.…”
Section: Data Processingmentioning
confidence: 99%